Infrastructure-based Networking for Autonomous Transportation Systems Using IEEE 802.11p - Sunyoto, Yulia; Rubin, Izhak (IEEE Vehicular Networking Conference, 2019)
We study infrastructure-based vehicular data networking for autonomous highway transportation systems. The infrastructure backbone consists of roadside units (RSUs) that act as access points for vehicles traveling along a segment of a highway system. The RSUs are interconnected by high-capacity point-to-point links. It is assumed that RSU transmissions reach all vehicles traveling along the highway. We present a data networking protocol that enables geocasting so that source vehicles aim to disseminate their data packets to vehicles that travel within a specified span from them. The dissemination route includes vehicle-to-infrastructure (V2I) and infrastructure-to-vehicle (I2V) wireless communication uplinks and downlinks. We study the performance behavior of the synthesized data network as a function of the average inter-RSU distance (i.e., the density of the RSU backbone). An IEEE 802.11p Medium Access Control (MAC) scheduling scheme is used for vehicles and RSUs to efficiently share the system's communications links. The data networking parameters configured for the synthesized network include the employed Modulation/Coding Schemes (MCS), the corresponding data rates, and vehicular and RSU transmit power levels. We evaluate the system's data throughput performance behavior, subject to the requirement that prescribed packet delay and delivery rate performance objectives are met. We show that system performance can be enhanced by the proper setting of vehicular and RSU transmit power levels. We provide analytical approximation to the effective transmit power levels, and verify them through simulation.